Organizational Change - Lazarova, Teodora (Economy and Business Yearbook, 2022)
In the recent months, the world has faced an unprecedented crisis, caused not only by economic factors, but also by many psychological ones, which arise from uncertainty and expectations for the future. The requirements for modern leaders are huge - not only to continue to manage the organization effectively, but also to cope with the difficulties that each member of the team has. In times of uncertainty, management is required to identify the key change and ensure the functioning of organizational processes and business operations. This report will focus on the challenges of today’s environment, which require the leader to be analytical, innovative and flexible. He must have the ability to lead the organization and people through the dynamics of a rapidly changing environment by influencing resistance to change. The report examines good practices in the field of organizational change and crisis management and provides specific recommendations for improving the efficiency and productivity of the organization.